Macroeconomic Stability and The Foreign Direct Investment in Tanzania (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: This study examined the relationship between FDI inflows and key macroeconomic indicators in Tanzania, including inflation, exchange rate, and trade openness.Design/Methodology/Approach: The study utilises time series data covering 50 years from 1970 to 2019. In the analysis, the key diagnostic tests such as the Augmented Dickey-Fuller (ADF) test and the Philip Peron (PP) tests for unit root/stationarity and the Johansen cointegration test to test for the long-run relationship between the variables were conducted before the primary analysis. The results of the diagnostic tests led the study into the Vector Error Correction Model (VECM), which estimates the relationship between the dependent and independent variables after discovering a long-run relationship among or between the variables.Findings: The VECM results showed that FDI is significantly determined by its lagged (Previous years) values and exchange rate in the short run. The results also showed a significant long-run relationship between exchange rate and FDI inflows, with other factors remaining constant. These results were consistent with prior assumptions and other findings from the literature.Research Limitation: The study considered FDI inflows in aggregate. This may have limited the analysis and discussions on the impact of the macroeconomic indicators on the general level of FDIs.Practical Implication: The study recommends that the country continue to promote FDI inflows while stabilising its exchange rate. The two will lead to more FDI inflows and good macroeconomic performance.Social Implication: These social implications demonstrate how exchange rate stability and FDI influence extend beyond pure economics to affect various aspects of Tanzanian society and community development.Originality/ Value: The paper's novelty lies in the improved understanding of variable interdependencies.
Keywords: Exchange rate. foreign direct investment. inflation. macroeconomic. stability. trade openness.